Women on the move: the neglected gender dimension of the brain drain - Jean-Christophe Dumont; John P. Martin; Gilles Spielvogel (Institute for the Study of Labor (IZA), 2007)
Two trends in international migration flows have attracted much attention recently: (i) the growing feminisation of migration flows; and (ii) the increasing selectivity of migration towards the highly skilled, which in turn has given rise to renewed concerns about the brain drain consequences for the sending countries. The two issues have not been considered jointly, however, mainly due to the lack of relevant data. This paper addresses this shortcoming by looking at the gender dimension of the brain drain, based on a new comparable data set that has been collected by the OECD and which allows us to identify people by country of residence, place of birth, gender and level of education. The evidence summarized in this paper shows that female migration to OECD countries has been increasing significantly in recent decades, so that migrant stocks are now more or less gender-balanced. A more surprising result is that this is also true for the highly skilled. Taking into account the fact that women still face an unequal access to tertiary education in many less developed countries, it appears that women are over-represented in the brain drain. This result is reinforced by econometric estimates showing that emigration of highly skilled women is higher, the poorer is their country of origin. This effect is also observed for men but to a lesser extent. It is not observed, however, at lower educational levels, where the traditional migration hump is identifiable. Econometric estimates also report a negative impact of emigration of highly skilled women on three key education and health indicators: infant mortality, under-5 mortality and secondary school enrolment rate by gender. These results raise concerns about a potentially significant negative impact of the female brain drain on the poorest countries.
Keywords: 330; Brain Drain; Geschlecht; Einwanderung; Frauen; OECD-Staaten